A Rapid and Efficient Method for Purifying High Quality Total RNA from Peaches (Prunus persica) for Functional Genomics Analyses - LEE MEISEL; BEATRIZ FONSECA; SUSANA GONZÁLEZ; RICARDO BAEZA-YATES; VERONICA CAMBIAZO; REINALDO CAMPOS; MAURICIO GONZALEZ; ARIEL ORELLANA; JULIO RETAMALES; HERMAN SILVA (Biological Research, 2005)
Prunus persica has been proposed as a genomic model for deciduous trees and the Rosaceae family. Optimized protocols for RNA isolation are necessary to further advance studies in this model species such that functional genomics analyses may be performed. Here we present an optimized protocol to rapidly and efficiently purify high quality total RNA from peach fruits (Prunus persica). Isolating high-quality RNA from fruit tissue is often difficult due to large quantities of polysaccharides and polyphenolic compounds that accumulate in this tissue and co-purify with the RNA. Here we demonstrate that a modified version of the method used to isolate RNA from pine trees and the woody plant Cinnamomun tenuipilum is ideal for isolating high quality RNA from the fruits of Prunus persica. This RNA may be used for many functional genomic based experiments such as RT-PCR and the construction of large-insert cDNA libraries.